The Role of Equality and Efficiency in Social Preferences - Ernst Fehr; Michael Naef; Klaus M. Schmidt (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2004)
Engelmann and Strobel (AER 2004) claim that a combination of efficiency seeking and minmax preferences dominates inequity aversion in simple dictator games. This result relies on a strong subject pool effect. The participants of their experiments were undergraduate students of economics and business administration who self-selected into their field of study and learned early on that efficiency is desirable. We show that for non-economists the preference for efficiency is much less pronounced. We also find a gender effect indicating that women are more egalitarian than men. However, perhaps surprisingly, the dominance of equality over efficiency is unrelated to political attitudes.
urn:nbn:de:bvb:19-epub-13518-6
Keywords: C7; C91; C92; D63; D64; 330; Social Preferences; Inequity Aversion; Efficiency Preferences